Hemoglobin H identification by high‐performance liquid chromatography in confirmed hemoglobin H disease. (18th May 2015) - Turley, E.; McFarlane, A.; Halchuk, L.; Verhovsek, M.
Summary: Introduction: Among hemoglobin (Hb) H disease cases diagnosed by DNA testing in our hemoglobinopathy laboratory, we have noted instances of unreported Hb H from high‐performance liquid chromatography (HPLC) results of referring laboratories. Methods: To characterize these issues, we identified all cases of genotypic Hb H disease diagnosed in our laboratory. HPLC chromatograms were reviewed to determine the presence and retention time of the Hb H peak. Results: Hemoglobin H was not reported in 24.2% of patients (23 of 95) with genotypic Hb H disease. The characteristic prerun peak of Hb H was present on review of all eight Variant or Variant II β‐thalassemia short‐program chromatograms. Elevated Hb F (≥3%) was reported in 14 cases. The Hb H peak was found in the Hb F window in 11 dual program cases. The incorrect identification of Hb H as elevated Hb F resulted in two testing referrals for 'δβ‐thalassemia'. Conclusions: Hemoglobin H may go unreported due to failure to examine for or recognize its peak on Variant or Variant II β‐thalassemia short‐program chromatograms. Elution of Hb H in the Hb F window resulted in misidentification of Hb H for Hb F and may indicate a Variant II HbA2 /HbA1C program software error. Our findings highlight the need for careful chromatogram inspection and clinical correlation in the diagnosis of Hb H disease.